DIFLUNISAL TRANSETHOSOMES FOR TRANSDERMAL DELIVERY: FORMULATION AND CHARACTERIZATION - APRIANTI, INDAH; ISKANDARSYAH; SETIAWAN, HERI (International Journal of Applied Pharmaceutics, 2023)
Objective: The work aimed to obtain an optimum formula of diflunisal transethosome by varying the types and concentrations of edge activators and optimizing the method of preparations. Methods: Sonication amplitude and sonication time were optimized based on vesicle size and polydispersity index (PDI). Transethosome formulation using different types and concentrations of edge activators would be characterized, including vesicle size, PDI, zeta potential, morphology, entrapment efficiency, and deformability index, which were carried out using the optimum sonication method to formulate the optimum formula. Results: The result indicates that 30% sonication amplitude for 5 min resulted in the smallest vesicle size with the lowest PDI. Also, F4 containing span 80 as edge activators at a concentration of 0.75% achieved the most favorable outcome, with a spherical shape, vesicle size of 75.32 nm, a PDI of 0.247, a zeta potential of-32.93mV, entrapment efficiency of 75.66% and deformability index of 40.45. Conclusion: Sonication time of 5 min with an amplitude of 30% is proven to produce optimum diflunisal transethosome, and in comparison to other vesicles, diflunisal transethosome using span 80 was able to have excellent vesicle characteristics, making it extremely promising to be developed as a transdermal delivery system.